If You Can Understand This Essay, Then You Have Moral Rights and Moral Duties - White Alan (Open Philosophy, 2020)
Alan Gewirth’s work on moral and political philosophy attracted a great deal of attention between 1978 and 2000, but has received very little attention since then. This essay aims to revive interest in Gewirth’s work by providing a more direct and straightforward version of his core argument for objective moral rights and duties and clarifying how a Gewirthian moral and political theory can proceed beyond the conclusion of the core argument.